Broadband sound absorption using multiple hybrid resonances of acoustic metasurfaces. (1st September 2022) - Ryoo, Hyeonbin; Jeon, Wonju
Highlights: Proposition of thin acoustic metasurface for broadband absorption of low-frequency sound via hybrid resonances at multiple target frequencies. Identification of physical mechanism of perfect absorption due to hybrid resonances in the near field of the metasurfaces. Systematic design of the metasurface whose supercell is partitioned into multiple unit cells for impedance matching at multiple target frequencies. Experimental verification of broadband absorption for fabricated samples in impedance tube. Abstract: Achieving broadband sound absorption in low-frequency ranges using thin acoustic materials has been a long-standing and challenging problem in acoustics. When using the existing acoustic materials such as porous and fibrous materials, they are inevitably thick for low-frequency sound absorption. In this study, we propose a thin acoustic metasurface for broadband absorption of low-frequency sound by using hybrid resonances at multiple target frequencies. Supercells of the proposed metasurface are partitioned into multiple unit cells, and each of them is composed of two adjacent subwavelength Helmholtz resonators for perfect sound absorption based on hybrid resonance at each target frequency. When the hybrid resonance is derived, the unit cell exhibits perfect sound absorption at the target frequency with the lower Q-factor than the existing absorbing structures with same thicknesses. To take this advantage, we herein propose design procedures for the proposed supercells to achieve perfect sound absorption based on hybrid resonances at multiple target frequencies. The designed supercells are fabricated by 3D printing apparatus and their absorbing performance is experimentally evaluated in impedance tube. A thin (< λ /11) acoustic metasurface composed of the designed supercells achieves high (>90%) absorption band over broad frequency range, whose relative Q-factor is reduced to about one third compared to the one of the designed unit cell for a single target frequency. This work opens possibilities for practical applications of acoustic metasurfaces in noise mitigation of various mechanical systems (e.g., home appliances and power transformers) in that the target frequencies of supercells are eligible to be customized for each system by using the proposed design procedures. Graphical abstract: Image, graphical abstract .